Increasing production and improving quality of lamb's meat through grassland cultivation and rotational management - Atti N.; Mahouachi M. (New approaches for grassland research in a context of climate and socio-economic changes, 2012)
The objective of this study was to evaluate lamb's growth and carcass characteristics on grazedgrassland compared to feedlot (FL) system. The grassland consists in two separate plots of green barley (GB) and perennial ryegrass (RG). Forty five lambs (14.8 ± 2.9 kg live weight (LW)) were divided into three groups. Two groups were conducted on rotational grazing with a stocking rate of 60 lambs per ha, one on GB and the other on RG and received daily 350 g of concentrate per lamb. The last group was conducted on FL with ryegrass hay and the same concentrate ad-libitum. The whole grass yield was higher for RG grassland than for GB one. The crude protein content of grass was higher for both species (14%) than ryegrass hay (8.5%). The mean daily herbage availability was 0.850 and 0.720 kg DM per lamb of RG and GB, respectively. Indoor daily intake was 450 g of hay and 650 g of concentrate per lamb. For 60 lambs, the owner needs 2.76 vs 2 ha in FL and grassland grazing system, respectively. Lamb's final LW and average daily gain were higher for grassland lambs (28.3 kg and 140 g) than FL ones (26.9 kg and 121 g). The whole LW gain was 176, 200 and 210 kg for FL, GB and RG treatments; which equivalent to 254, 399 and 420 kg LW gain per ha in FL, GB and RG, respectively. Furthermore, grassland lamb's carcasses were less adipose (18%) and contain more muscle (57%) than that of FL (26% fat and 51 % muscle). Grazing grassland with rotational management leads to higher lamb production with higher muscle and lower fat carcass concentrations than FL system. This production system is more economic and resulted in lamb meat with high nutritional characteristics.
14. Meeting of the FAO-CIHEAM Subnetwork on Mediterranean Forages and Fodder Crops, 2012/10/03-06, Samsun (Turkey)